Leveraging Educational Technology to Enhance Health Literacy: Insights from 21st Century Case Studies - Sutrisman, Henny; Askrening; Yunus, Reni; Padua, Shirley A.; Prihartanto, Adrianus; Kusumo, Bayu; Simanjuntak, Rosmerry (International Journal of Scientific Research and Management (IJSRM), 2025)
Health literacy is essential for enabling individuals to access, understand, and utilize health information to promote better health outcomes. This study aims to explore the role of educational technology in improving health literacy, particularly in 21st-century health education.A systematic review was conducted using 16 international journals from 2008 to 2024, selected from Google Scholar and Scopus. The focus was on analyzing interventions employing technologies such as virtual reality (VR), multimedia platforms, and interactive tools to enhance health literacy across diverse populations.The results indicate that VR-based interventions improved knowledge retention, skill acquisition, and behavioral changes, including smoking cessation. Multimedia applications tailored for specific groups showed positive impacts on knowledge enhancement and engagement. However, accessibility challenges and technological literacy gaps remain barriers. Studies highlight the importance of immersive, culturally relevant, and targeted educational approaches to achieve better outcomes.Educational technology presents significant potential for advancing health literacy, especially among vulnerable populations. Tailored interventions leveraging innovative technologies can support meaningful learning experiences and foster positive health behaviors.